Intestinal histology and immune status of semi-anemic piglets fed lactoferrin, meat, or meat extract - Rapisura-Flores, Josephine A.; Purchas, Roger W.; Thomas, David G.; Wilkinson, Brian H.P; Rutherfurd-Markwick, Kay; Morel, Patrick C.H (2019)
This study assessed the effects of dietary lactoferrin, meat, or meat extract on immune status and small intestine morphology of 24 three-week-old semi-anemic piglets (six per group) over 28 days, after a one week acclimatization period. Blood samples collected from the piglets at 4 and 8 weeks of age were subjected to whole-blood proliferation and phagocytic activity assays. The leukocyte phagocytic activity and lymphocyte cell proliferative responses of the piglets to concanavalin A and phytohemagglutinin were significantly (p<0.05) improved by the meat-extract diet. This demonstrated that meat extract is a potential immuno-modulating feed ingredient particularly after the period of weaning when piglets are highly susceptible to infection. For intestinal histology, each piglet was euthanized at 8 weeks of age while under anaesthesia and had its small intestine removed. No diet effects were observed for some histological parameters (villus height, crypt depth, and mucosal thickness). However, meat and meat-extract diets significantly (p=0.003) increased the number of goblet cells / 100μm of villous epithelium, which suggests that the meat extract and meat diets stimulated mucin secretion. (Author's abstract)